i-Soc: An Info-Sociological Approach to Structural–Agent Causal Symmetry - Shing-Chung Jonathan Yam (Philosophies, 2020)
In this article, I discuss the sociality of information flow by investigating a momentous yet often-neglected side of it—the reinforcing info-causal loops between habitus and structures. I treat habitus as a principled agent and explain how structure sustains itself (under the framework of Fiske and Pinker et al.) by upholding principles as goals or reducing them into subroutines (goal subjugation). At the structural level, four dominant categorical schemes—game theory, network analysis, systems functionalism, and field theory—are investigated for the characteristic information flow that they can capture. The result is an info-sociological approach that acknowledges causal symmetry between structure and agents.